2015
DOI: 10.5897/ajar2015.9859
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among accessions of Carthamus tinctorius L. by morphoagronomic traits

Abstract: Safflower (Carthamus tinctorius L.) is a crop that produces oil with high content of oleic and linoleic acids, which has great quality for human consumption and industrial use, such as in biodiesel production, and cosmetics and pharmaceuticals. The objective of this study was to quantify the genetic diversity among 20 safflower genotypes by morphological characteristics. The genotypes were grouped into nine groups based on the measurements of genetic divergence obtained by means of Mahalanobis distance (D 2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…Characteristics related to plant morphology, such as plant height and the number of branches and heads, presented low heritability. Unlike this study, Silva et al (2015), Golkar et al (2017), andOlivo et al (2020) observed high values of heritability for plant morphology characteristics. The low heritability values are due to the high environmental effect.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Characteristics related to plant morphology, such as plant height and the number of branches and heads, presented low heritability. Unlike this study, Silva et al (2015), Golkar et al (2017), andOlivo et al (2020) observed high values of heritability for plant morphology characteristics. The low heritability values are due to the high environmental effect.…”
Section: Discussioncontrasting
confidence: 95%
“…The oil content is highly influenced by the genetic characteristics of the plants, climatic and soil conditions, and crop management. Under Brazilian conditions, Silva et al (2015), reported average values of oil content from 20.7 to 30.5% and Bortolheiro and Silva (2017) from 19.91 to 30.32%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations